2020
DOI: 10.1155/2020/8878125
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Desorption Characteristics of Coalbed Methane under Variable Loading and Temperature in Deep and High Geothermal Mine

Abstract: Due to the influence of deep high stress, geothermal heat, and other factors, the law of desorption of methane in coal seams is more complicated in the process of mining deep coal seams, which is prone to methane over-limit, coal and gas outburst, and other accidents. In order to study the desorption characteristics of coalbed methane under different loading and temperature conditions, the desorption tests at different deformation stages of coal containing methane were carried out in the process of loading-ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A coal mine can produce 5 million tons of coal every year, which belongs to the coal and gas outburst mine, and there is a large amount of coal seam gas in the coal seam. According to the report of field supplement survey and the measurement data of coal seam gas parameters, the total CBM reserves of the coal mine are 24.36 billion m 3 , of which the recoverable coal seam reserves are 12.9 billion m 3 , the reserves of the non-recoverable adjacent coal seams within the mining impact range of the recoverable coal seam are 7.4 billion m 3 , and the surrounding rock reserves are 4.06 billion m 3 .…”
Section: Investigation Of Gas Source In Coal Minementioning
confidence: 99%
See 3 more Smart Citations
“…A coal mine can produce 5 million tons of coal every year, which belongs to the coal and gas outburst mine, and there is a large amount of coal seam gas in the coal seam. According to the report of field supplement survey and the measurement data of coal seam gas parameters, the total CBM reserves of the coal mine are 24.36 billion m 3 , of which the recoverable coal seam reserves are 12.9 billion m 3 , the reserves of the non-recoverable adjacent coal seams within the mining impact range of the recoverable coal seam are 7.4 billion m 3 , and the surrounding rock reserves are 4.06 billion m 3 .…”
Section: Investigation Of Gas Source In Coal Minementioning
confidence: 99%
“…According to the information provided by the coal mine ventilation department, in 2018, the low concentration coal bed methane extracted from the coal seam in the mine was 27.24 million m 3 , with a concentration of about 5%, which was completely drained. The coal bed methane extracted from adjacent strata is 61.46 million m 3 , the concentration is more than 35%, and the utilization is 20.77 million m 3 . It is mainly used for heating in mining area, bathing, central air shaft heating, coal bed methane driven air conditioning unit, coal bed methane power generation, slime drying, canteen gas, and gas for nearby residents, etc.…”
Section: Investigation Of Gas Source In Coal Minementioning
confidence: 99%
See 2 more Smart Citations
“…Temperature affects not only gas adsorption but also desorption and diffusion. Several researchers have revealed that raising the temperature of coal seams can promote the desorption and diffusion of methane. Among these studies, those of Tang et al, Li et al, and Jiang et al are the most cited. ,, Their experimental conditions are shown in Table . All these experiments have shown that a higher constant desorption temperature was correlated with a greater desorption content.…”
Section: Introductionmentioning
confidence: 99%